POLITICS AND INVESTOR CONFIDENCE: THE BALTIC STATES DURING THE CRISIS - Kuokštis, Vytautas (Politologija, 2015)
The paper seeks to explain the differences as to how successfully the three Baltic countries managed the economic crisis between 2008 and the first half of 2010. More specifically, it analyzes investors’ confidence, Estonia being the most successful country in this regard, Latvia the least (the only country that applied for aid from the International Monetary Fund), while Lithuania staying in between. The paper aims to take into account the differences (and similarities) between the Baltic countries as well as emphasize the importance of political-institutional factors in explaining investors’ confidence. The importance of investors’ confidence as is discussed and different ways of measuring it are reviewed. Moreover, the relevance of political-institutional factors in explaining investors’ confidence is established from the theoretical point of view. Based on existing literature, a number of explanatory factors are distinguished, namely electoral processes, non-electoral pressures on government, government stability as well as the quality of informal institutions. The paper argues that Latvia was indeed in a significantly worse situation in terms of economic pre-crisis vulnerabilities than Lithuania and Estonia, both of which had certain, albeit different, economic advantages. The main difference between Lithuania and Estonia emerges comparing political-institutional, rather than purely economic, factors: Estonia was better placed in terms of electoral cycles, the extent of non-electoral pressures, and – most importantly – better institutions (governance quality, corruption level, trust in political institutions). Both Latvia and Lithuania found themselves in a significantly worse situation regarding political-institutional factors.